Um jogo sério para apoio ao ensino de modelagem de processo de software baseado em mapas conceituais: uma avaliação experimental - CHAVES, Rafael Oliveira (Universidade Federal do Pará, 2017)
Software process modeling (SPM) is an important area of software engineering because it provides a basis for managing, automating, and supporting software process improvement (SPI). Teaching SPM is a challenging task, mainly because it lays great emphasis on theory and offers few practical exercises. Furthermore, as yet few teaching approaches have aimed at teaching SPM by introducing innovative features, such as games. The use of games has mainly been focused on other areas of software engineering, for example software project management. In an attempt to fill this gap, this paper describes a formal experiment carried out to assess the learning effectiveness of a serious game (DesigMPS), designed to support the teaching of SPM, and to compare game-based learning with a project-based learning method. In the DesigMPS game, the student models a software process from an SPI perspective, based on the Brazilian SPI model (MPS.BR). Also features of the game were analyzed as: appropriateness in terms of content relevance, sufficiency, degree of difficulty, sequence, teaching method; engagement; strengths and weakness. The results indicate that playing the game can have a positive learning effectiveness (statistically significant difference) on the cognitive levels of understanding and applying, according to the revised version of Bloom's taxonomy of educational objectives, despite some weaknesses as: the lack of “help” on the use of the game and the lack of clearer instructional feedback with explanations regarding the causes of errors. Also, there is positive learning effectiveness (statistically significant difference) when compared to the PBL on the applying level, but no significant difference on the understanding level. Most students considered that the game is engaging and relevant concerning the content of Software Quality course. Based on the results the game could be an option to teach SPM.